Investigation of Harmonine inhibition of NMDA receptors - Brown Coker, Dennon-jay (2023)
N-methyl-D-aspartate receptors (NMDAR) is a critical ionotropic receptor in excitatory neurotransmission, it is a co-agonist receptor with a hetero tetrameric structure. It strengthens synaptic connections as it is involved in long term potentiation and is pivotal for learning and memory. GluN2A and GluN2B are crucial NMDAR subunits they differ in morphology and amino acids sequence which results in different Ca2+ currents, which are useful in different neural processes. NMDAR dysfunction can cause neurotoxicity, and this is seen in the Neurodegenerative disease, Alzheimer’s disease (AD). The pathological hallmarks of AD, amyloid plaques interact with glutamate transporters in the tri-synapse. This pathway is one of many pathologies that lead to the cerebral atrophy seen in AD. Memantine is a FDA approved drug treatment for AD and used to treat moderate to severe symptoms. Research by Patel 2018 has shown that harmonine, an alkaloid produced by the harlequin ladybird, Harmonia axyridis, a key component of the organism's chemical defence can inhibit NMDAR activity. This inhibition makes harmonine a target for research as therapeutic treatment of AD. In this study, the aim is to study the effects of harmonine on human NMDAR clones. Two-electrode voltage clamp was used to examine the effects of memantine and harmonine in a concentration-dependent manner, in Xenopus oocytes expressing the NMDAR clones. The IC50 values revealed that harmonine blocks NMDAR in a concentration-dependent manner and is more potent than memantine at a membrane potential of -75 mV.